Interlocking directorates and family firm performance: an emerging market’s perspective - Watkins-Fassler, Karen; Rodríguez-Ariza, Lázaro; Fernández-Pérez, Virginia; Briano-Turrent, Guadalupe del Carmen (Journal of Family Business Management, 2024)
Purpose: This study analyses interlocking directorates from the perspective of an emerging market, Mexico, where formal institutions are weak, and family firms with high ownership concentration dominate. It responds to recent calls in the literature on interlocks, which urge the differentiation between family and non-family businesses and to complete more research on emerging economies. Design/methodology/approach: A database was constructed for 89 non-financial companies (52 family-owned) listed on the Mexican Stock Exchange (BMV) from 2001 to 2014. This period includes normal times and an episode of financial crisis (2009–2010). To test the hypotheses, a dynamic panel model (in two stages) is used, applying GMM. Findings: In normal times, the advantages of Board Chairman (COB) interlocks for the performance of publicly traded Mexican family firms are obtained regardless of the weak formal institutional environment. By contrast, during financial crisis, interlocking family COBs are more likely to jointly expropriate minority shareholders with actions that further their family objectives, which mitigates the positive effect of interlocks on performance. These findings contrast with the insignificant effects of COB interlocks found for non-family corporates. Originality/value: A new framework is proposed which, through agency theory, finds points of concordance among resource dependence and class hegemony theories, to understand the effect of interlocking directorates on the performance of family firms operating in Mexico. The results of the empirical exercise for family companies listed on BMV during normal and financial crisis periods suggest its applicability.
Keywords: agency theory; class hegemony theory; emerging markets; family firm performance; interlocking directorates; Mexico; resource dependence theory; Scopus; Emerging